Analisis Yuridis Terhadap Penyelesaian Kasus Aborsi yang Dilakukan Anak di Bawah Umur - Bayu Rosa Ramdhani Pasya (Jurnal Hukum Caraka Justitia, 2026)
The phenomenon of abortion carried out by minors has become a crucial issue in the realm of law and child protection in Indonesia. This problem often arises due to unwanted pregnancies, frequently rooted in sexual violence or a lack of understanding regarding reproductive health. This study aims to analyze the legal resolution of abortion cases committed by minors from a juridical perspective, both in Indonesian positive criminal law and Islamic criminal law. The research uses a normative juridical approach by analyzing laws and regulations, jurisprudence, and relevant literature. The findings reveal that although Indonesian law criminalizes abortion, certain exceptions are allowed, such as in cases of rape that endanger the physical and mental health of the victim. On the other hand, Islamic criminal law provides sanctions based on the gestational age and the reason for the abortion. In practice, case resolution tends to consider the offender's age, psychological condition, and coercive elements. This study recommends the need for a restorative approach that prioritizes child protection, rehabilitation, and sexual education as preventive efforts.